Language Models vs. Human Experts on Professional Knowledge Benchmarks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 12 peer-reviewed papers addressing the following research question: How do language models compare to human experts on professional knowledge and science benchmarks v14. 11 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.0/10. This report is a machine-generated literature synthesis and does not constitute original research.
Machine-generated literature synthesis.